COMBINED BIOLOGICAL-PHOTOCATALYTIC TREATMENT FOR THE MINERALIZATION OF A MIXTURE OF CHLOROPHENOLS IN AN ELECTROLYTE-CONTAINING MODEL WATER AND SPONTANEOUS SEDIMENTATION OF TITANIUM DIOXIDE - Dhanus Suryaman; Kiyoshi Hasegawa; Shigehiro Kagaya; Toshiaki Yoshimura (Indonesian Journal of Chemistry, 2007)
To shorten the biological treating time and to examine the effect of electrolytes in a model water on the photocatalytic treatment, the combined biological-photocatalytic treatment was evaluated for removal of a mixture (total: 100 mg L-1, each: 25 mg L-1) of 2-chlorophenol (2-CP), 2,4-dichlorophenol (2,4-DCP), 2,4,5-trichlorophenol (2,4,5-TCP), and pentachlorophenol (PCP) in tap water. The mineralization of the four phenols was performed by a flow (biological treatment)-circulative flow (photocatalytic treatment) operation under black light and sunlight irradiations. After a large portion of biodegradable 2-CP and 2,4-DCP, and around half amount of slightly biodegradable 2,4,5-TCP were removed by the biological treatment, the remained three chlorophenols, biorecalcitrant PCP, and  biodegradation products were completely removed by the subsequent photocatalytic treatment. The combined treatment significantly shortened the degradation time only the biotreatment. High circulative flow rate (600 mL min-1) enabled for TiO2 particles to completely suspend in a tubular photoreactor and resulted in high removals of chlorophenols and TOC. Sunlight irradiation was successfully used and the saving of the electric energy of black light was possible. Since TiO2 particles in the tap water spontaneously sedimented on standing after the photocatalytic treatment, the combined system can be operated by integrating it with the TiO2 separation.